Avaliação fisioterapêutica do complexo do ombro em pacientes com Diabetes Mellitus - Nardini, Lívia Bernardi (Universidade Federal de São Carlos, 2024)
Introduction: Some studies have already indicated an association between Diabetes Mellitus (DM) and musculoskeletal alterations, particularly in the shoulder complex. Although the high prevalence of frozen shoulder in individuals with DM is well described in the literature, studies that analyzed shoulder alterations more broadly and functionally in this population are still scarce. Objective: This study aimed to compare shoulder pain and function between individuals with and without DM. Methods: A cross-sectional study was conducted involving 26 participants divided equally into two groups: 13 with DM and 13 controls without DM. Sociodemographic data and lifestyle habits were collected. Shoulder pain and function (using the SPADI questionnaire); active and passive range of motion of shoulder flexion, medial rotation, and lateral rotation; muscle function of shoulder flexors, medial and lateral rotators, and serratus anterior; and functional performance of the upper limb (assessed by TFAST) were evaluated and compared between groups. Normality of data was assessed using the Shapiro-Wilk test. Student's parametric t-test was applied when data showed normal distribution to compare dependent variables between the two groups. For data that did not show normal distribution, the non-parametric Mann-Whitney U test was used for comparison. The significance level for all analyses was set at 5%. Results: No statistically significant differences were observed in shoulder pain, disability, range of motion, muscle strength, or functional performance between the DM and control groups. A slightly higher percentage of participants in the DM group reported shoulder pain compared to the control group (46.2% vs. 38.5%), but this difference did not reach statistical significance. Conclusion: Our findings indicate that the association between DM and musculoskeletal disorders in the shoulder may be more complex than initially presumed, suggesting the influence of intermediate and multiple factors. Additionally, the presence of healthy lifestyle habits, such as physical activity and absence of smoking, in the sample of this study specifically may have influenced the results.
Physiotherapeutic evaluation of the shoulder complex in patients with Diabetes Mellitus
Keywords: Doenças metabólicas; Dor; Função; Membro superior; OUTROS